2015
DOI: 10.1080/2153599x.2015.1029513
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative associations between adolescents' religiousness and health behaviors via self-regulation

Abstract: It has been proposed that self-regulation may be the explanatory mechanism for the relation between religiousness and positive health behaviors. However, different religious motivations have differential effects on a variety of health related outcomes, which may explain the adverse effects of religiousness found in some studies. The current study hypothesized that higher identification as religious motivation would be linked to higher health-promoting behavior and lower health-risk behavior through higher self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…This perspective has been empirically justified by demonstrating that religious undergraduates (measured via intrinsic religiousness) report more consideration for their future in current decision making than non-religious undergraduates (Oner-Ozkan, 2007). This evidence has been further corroborated in a longitudinal analysis of sequential mediation linking religiousness → afterlife beliefs → future orientation → substance use behaviors, after controlling for initial levels of substance use in a sample of adolescents (Holmes & Kim-Spoon, 2015). Specifically, the findings directly indicated that higher religiousness (measured as a composite of organizational and personal religiousness and private practices) was associated with lower EP through higher afterlife beliefs as afterlife beliefs may lead an adolescent to think more about the future, which ultimately may deter cigarette and marijuana use (indirect effects 95% CI for b * = [−.05, −.003] for cigarette use and 95% CI for b * = [−.06, −.001] for marijuana use).…”
Section: Factors Associating Adolescents’ Religiousness and Spiritualmentioning
confidence: 68%
See 4 more Smart Citations
“…This perspective has been empirically justified by demonstrating that religious undergraduates (measured via intrinsic religiousness) report more consideration for their future in current decision making than non-religious undergraduates (Oner-Ozkan, 2007). This evidence has been further corroborated in a longitudinal analysis of sequential mediation linking religiousness → afterlife beliefs → future orientation → substance use behaviors, after controlling for initial levels of substance use in a sample of adolescents (Holmes & Kim-Spoon, 2015). Specifically, the findings directly indicated that higher religiousness (measured as a composite of organizational and personal religiousness and private practices) was associated with lower EP through higher afterlife beliefs as afterlife beliefs may lead an adolescent to think more about the future, which ultimately may deter cigarette and marijuana use (indirect effects 95% CI for b * = [−.05, −.003] for cigarette use and 95% CI for b * = [−.06, −.001] for marijuana use).…”
Section: Factors Associating Adolescents’ Religiousness and Spiritualmentioning
confidence: 68%
“…Because behaviors that are regulated by introjection feel less volitional and may create greater conflict, introjected beliefs are less assimilated and the behaviors they motivate do not feel self-determined. Indeed, Holmes and Kim-Spoon (in press) found that identification of religious values were associated with lower levels of substance use among adolescents, whereas introjection of religious values were associated with higher levels of substance use even after controlling for the effects of general religiousness (measured by a composite of organizational and personal religiousness and private practices). Similarly, another study included an exploration in differences of hazardous alcohol use between three latent profiles of religiousness (Jankowski et al, 2015).…”
Section: Definitions and Measurement Of Religiousness And Spiritualitymentioning
confidence: 99%
See 3 more Smart Citations